Perbedaan Pengaruh Latihan Core Muscle (Variasi Plank dan Variasi Squat) terhadap Peningatan Hasil Lemparan Ke dalam Pemain Akademi Arema FC U-16 - Riko Wahyu Prasetiyo; Mahmud Yunus; Heri Purnaman Pribadi (Jurnal Mahasiswa Kreatif, 2024)
Football requires players to master the basic techniques of playing football, one of which is the Throw-In. Football players can improve throw-ins through Core Muscle Training with plank variations and squat variations. The Arema FC U16 Academy has a specific training program to improve Throw-In abilities. This research method uses a quasi-experimental method with a "two group pretest posttest design" design. The research population is 38 Arema FC U16 Academy players and a sample of 30 players with a sampling technique using random sampling. This research was carried out in the ITN 2 Malang field and was carried out over 16 meetings. The instrument in this research used a throw in test with a reliability value of 0.73 and a validity of 0.78. The results of this study showed that both groups had a normal distribution with a significance value of 0.938 in the plank group pretest, 0.647 in the plank group posttest, while the squat group pretest had a significance value of 0.465 and the squat group posttest had a significance value of 0.084. The homogeneity test for the two groups has a significance value of 0.391. The hypothesis test of the paired sample t test for the plank group has a significance value of 0.001 and the paired sample t test for the squat group has a significance value of 0.001. while the independent t test between the two groups has a significant difference with a sig value of 0.000, it is known that the plank group has a more significant influence with the difference in the value of the plank group. Based on the results of the paired sample t test and independent t test, it is known that the plank group has a significant difference in influencing the increase in throw-in results for Arema FC U16 Academy players.